1992
DOI: 10.1111/j.1365-2559.1992.tb00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial oesophageal leiomyomatosis and nephropathy

Abstract: Four female members of the same family suffering from a rare combination of oesophageal leiomyomatosis and an Alport-like nephropathy are described. The disease is characterized by marked thickening of the oesophageal wall, usually also involving the proximal stomach, with or without discernible leiomyomatous nodule formation. All cases were treated surgically by oesophagectomy with symptomatic relief, and there was no evidence of recurrence on follow-up (2-37 years). The syndrome appears to be dominantly inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…Although there were multiple myomatous nodules, they were confluent but should be differentiated from the multiple esophageal leiomyomatosis which presents with multiple separate nodules that can be shelled out individually. Diffuse esophageal leiomyomatosis may be associated with Alport’s syndrome (cataract, deafness and hematuria), and familial leiomyomatosis of the esophagus is believed to be dominantly inherited [13, 14, 17, 18, 22]. Our patient had multiple confluent myomatous nodules similar to that which Kabuto et al [3]reported as diffuse leiomyomatosis of the esophagus.…”
Section: Discussionsupporting
confidence: 64%
“…Although there were multiple myomatous nodules, they were confluent but should be differentiated from the multiple esophageal leiomyomatosis which presents with multiple separate nodules that can be shelled out individually. Diffuse esophageal leiomyomatosis may be associated with Alport’s syndrome (cataract, deafness and hematuria), and familial leiomyomatosis of the esophagus is believed to be dominantly inherited [13, 14, 17, 18, 22]. Our patient had multiple confluent myomatous nodules similar to that which Kabuto et al [3]reported as diffuse leiomyomatosis of the esophagus.…”
Section: Discussionsupporting
confidence: 64%
“…Alport syndromeassociated esophageal leiomyomas may already manifest in childhood and occur in siblings. [63][64][65] Interestingly, similar somatic changes involving collagen 4 gene have also been detected in sporadic esophageal leiomyomas indicating that disruption of basement membrane collagen may be related their pathogenesis. 66 Even rarer syndrome associated with GI mural leiomyoma is multiple endocrine neoplasia type 1 (also known as Werner syndrome, with pituitary, parathyroid, and pancreatic/duodenal neuroendocrine tumors, with mutated MEN1 tumor-suppressor gene).…”
Section: Gastrointestinal Smooth Muscle Tumorsmentioning
confidence: 69%
“…However, two different disease complexes involving esophageal leiomyomatosis have been described. The first is the association of esophageal leiomyomatosis and Alport’s syndrome in children [13, 14, 15]. The second, which is more pertinent to our patient, is the association of esophageal leiomyomatosis and vulvar leiomyomas.…”
Section: Discussionmentioning
confidence: 99%